Hot spots and trends in recreational landscape research since the 21st century: A CiteSpace-based visual analysis - Wang, Fanglong; Hussain, Norhuzailin; Abdul Aziz, Faziawati (Taylor & Francis Online, 2023)
The purpose of this paper is to analyze the article publication volume, keyword co-occurrence, keyword clustering, and keyword mutation of recreational landscape using CiteSpace visual analysis software and to put forward the research hotspots and similarities and differences between Chinese and international recreational landscape since the 21st century. In this paper, 583 articles from the China Knowledge Network Database (CNKI) and 3227 articles from the Scopus Database are used as samples for comparative analyses to provide a scientific basis and valuable theoretical references for the research on the recreational landscape. The study shows that: 1. China is relatively lagging in recreational landscape research, with few core journals. Although international recreational landscape research started relatively early, the number of articles at the beginning stage is also relatively small. 2. The hotspots of international journals are biodiversity, urban parks, forest recreation, and the planning and management of recreational landscapes. Chinese journals focus on the theory of recreational landscape, forest recreation, and recreational landscape design of nursing institutions and hospitals. 3. With the more comprehensive coverage of recreational landscape design, future research on recreational landscapes will be more diversified and standardized, with more emphasis on the specific needs of recreational landscapes of a particular group of people as the object of research.